Ethnosilvicultural knowledge: A promising foundation for integrating non-timber forest products into forest management - Gautam, Krishna H; Watanabe, Teiji (Himalayan Journal of Sciences, 2006)
Reconciling the multiple roles of forest resources is one of the unresolved challenges for sustainable forestry, but forest management practices are still focussed on timber production. The urgent need for the integration of non-timber forest products into mainstream forestry has, however, been widely acknowledged. Ethnosilvicultural knowledge from Canadian Aboriginal communities and community forest users of Nepal is assessed in the context of multiple-product forest management. Both cases reveal a wealth of such knowledge, indicating the opportunities for integrating non-timber forest product management in mainstream forestry. It is argued that ethnosilviculture is valuable in sustaining ecological processes as well as cultural heritages and traditional rural livelihoods. Broad guidelines for acquiring ethnosilviculture knowledge are also suggested.Himalayan Journal of Sciences 2(3): 55-58, 2004